BILINGUALISM, IT IS A POWERING IN YOUNG LEARNERS IN PEMATANG SIANTRA TROUGH TEACHING AND LEARNING PROCESS - Indra Jayanti Damanik; Natanael Saragih (Bilingual : Jurnal Pendidikan Bahasa Inggris, 2020)
Learning a language is influenced by a variety of factors. Learning English is important to children that will help them in achieving their full potential in the future. If they have the right techniques, they can learn English quickly and effectively. Applying a good technique is important that they have to learn English which is by practicing and using the language fluently. Learning must not be stressful for the children. The process should be simulating with a interesting technique by the teacher. So, their studies should make reading, listening, and speaking in English practice naturally. As a confidence to develops, the children can learn more and speak English improve their English. This paper will discusses about the way to teach the young learners in Pematang Siantar. These are purposed for children to be able to learn English effectively with the fun situation and variety program that children need in practicing a language. At the last, this paper discuss about how to guarantee the children learning English by using a simple techniques that can absolutely make the teachers’ responsibility in teaching more fun and satisfying in the result of student, and the teaching process will be expected that the teachers will have an idea to be the most inspiring teachers that possibly can applying in teaching and learning process